Selected Papers from the 8th International Symposium on Electric and Magnetic Fields. - Dular, Patrick (COMPEL: Volume 29, Edition 6., 2010)
The purpose of the EMF Symposium is to build a bridge between the recent advances of research in numerical modelling of electromagnetic fields and the growing number of industrial problems requiring such techniques. A limited number of 24 papers was selected by the EMF 2009 Scientific Committee for publication in this e-book of the COMPEL Journal.